The family Rhizobiaceae - Carrareto Alves, Lucia Maria [UNESP]; De Souza, Jackson Antônio Marcondes [UNESP]; Varani, Alessandro De Mello [UNESP]; Lemos, Eliana Gertrudes De Macedo [UNESP] (Springer Nature, 2014)
Rhizobiaceae is a family of Rhizobiales order into Alphaproteobacteria class that presents genera associated with soil and planta hosts. Rhizobium is the type genus and encompasses the largest number of species into the family. Taxonomy is mostly supported by phylogenetic analyses based on 16S rRNA sequences and nomenclature in Rhizobiaceae is one issue that has caused much discussion. Bacteria are phenotypically heterogeneous, predominately aerobic, and Gram-negative rod-shaped. Many species present large plasmids which harbor a large proportion of genome generally including genes involved in interaction with specific hosts. Some members of the Rhizobiaceae family are characterized by their ability to establish symbiotic associations with host plants and develop the process of biological nitrogen fixation. In contrast, others are able to establish pathogenicity against plants. Both skills can be exploited for applied purposes. The selection of efficient strains from Rhizobium and Ensifer designed to plant inoculants is one of important research viewing the production of microbial inoculants to help plant development. Considering Agrobacterium tumesfaciens, the management of its natural ability to transform plants is directed to obtaining disarmed strains and clone vectors widely applied to recombinant DNA technology and plant biotechnology. Finally, some genera in Rhizobiaceae family have intriguing metabolisms which allow degradation of potentially toxic molecules and thus could be applied as biomarkers or in bioremediation.